BOOK REVIEW: Sándor Nagy, “«Engesztelhetetlen gyűlölet». Válás Budapesten (1850-1914)”. [“Unappeasable hatred, appeasable law. The role of lawmaking in the growth of divorce numbers in Budapest (1850-1914]”, Budapest: Budapest Főváros Levéltára, 2018 - SZABÓ, Zsolt (Studia Universitatis Babeș-Bolyai Historia, 2019)
The process of modernization brought many social changes with itself, one of these being the rapid increase in the number of divorces in society. This phenomenon is usually explained through social and economic factors. The book that is the subject of this review does not call into question the importance of these factors, but wants to add a new one: a judicial factor, asking how legal regulation can prevent or increase the number of divorces in a certain society. The author of the book is Sándor Nagy, a historian and archivist, employee of the Budapest City Archives.